Endoscopic pediatric neurosurgery: implications for anesthesia. Issue 7 (12th April 2014) - Meier, Petra M.; Guzman, Raphael; Erb, Thomas O.; Soriano, Sulpicio
Summary Endoscopic surgery is increasingly utilized in neurosurgery for all pediatric age groups. Endoscopic intraventricular neurosurgery represents a unique approach to intracranial pathology but may cause a unique set of limitations and potential complications. Important endoscopic neurosurgical techniques and their indications, perioperative anesthesia management, complications, and success rates are reviewed with special emphasis on endoscopic third ventriculostomy and endoscopic‐assisted strip craniectomy in early infancy. Despite encouraging short‐ and long‐term results of early pediatric endoscopic neurosurgery, multicenter randomized studies will be needed to further determine safety and the effect on cognitive development and quality of life.